8x^2 -2x -3 = 0
----------------------
4x ---- -3
-----x-----
2x ---- 1
-----------------------
cross multiply = -2x
-----------------------
8x^2 -2x -3 = (4x-3)(2x+1)
(4x-3)(2x+1) = 0
x= -1/2 or 3/4
2007-02-03 05:26:18
·
answer #1
·
answered by Geinius 3
·
0⤊
0⤋
I am assuming that this expression is equal to zero and you want to solve for x:
8x^2 -2x -3 = 0
the easy way on this expression would be to factor it:
(2x+1)(4x-3) = 0
this can be true only if one of the factors are equal to zero
set each factor equal to zero and solve for x:
2x+1 = 0 therefor x = -1/2
4x-3 = 0 therefor x= 3/4
the above are the two solutions of the given expression.
you get 2 solutions or roots because x was to the second power in the given problem.
2007-02-03 05:38:39
·
answer #2
·
answered by bignose68 4
·
0⤊
0⤋
You could use the quadratic formula.
Heres the website where you can find the formula..It's too difficult to type here. http://www.purplemath.com/modules/solvquad4.htm
so in your equation 8x^2 - 2x -3, a=8, b= -8, and c= -3
so where its -b on the formula, ur going to plug in -(-8) so it will become positive 8. then under the square root its (-8)^2 - 4(8) (-3)
understand? you're just plugging in and then on the bottom ur gonna plug in 2(8). and then solve. remember u need to do -(-8) + the square root stuff divided by the 2(8) and then u need to do
-(-8) - the square root stuff divided by the 2(8).
Im not very good at explaining but i hope it helps a little bit!
2007-02-03 05:20:53
·
answer #3
·
answered by JhoAnNaBaNAnA 1
·
0⤊
0⤋
I assume the equation is 8x^2 -2x -3=0
The quickest way is to use the equation for the solving of a quadratic equation:
x= -b+-sqrt (b^2-4*a*c)
-------------------------
2a
Where a =8, b=-2 and c=-3 and sqrt is the square root.
x= +2+- sqrt (4+4*8*3)
-------------------------
16
This simplifies to
x= +2+-sqrt (100)
---------------------
16
Therefore x roots are
x= (+2+10 )/16 and x= (+2-10)/16
The roots are 12/16 and -8/16, which simplifies to 3/4 and -1/2.
2007-02-03 05:24:04
·
answer #4
·
answered by The exclamation mark 6
·
0⤊
0⤋
8x^2-2x-3=0
(4x-3)(2x+1)=0
4x-3=0
4x=3
x=3/4
2x+1=0
2x=-1
x=-1/2
ok its hard to explain, but here goes. you have to factor the polynomial using FOIL. FOIL stands for First-Inner-Outer-Last.
(4x-3) (2x+1)
The "First" values are 4x and 2x. We multiply these two to get 8x^2, which is the first value of the polynomial.
The "Outer" values are 4x and 1. We multiply these and get 4x
The "Inner" values are -3 and 2x. We multiply these and get -6x
Now when we add the two products together to get +4x-6x we get -2x, which is the middle term of the polynomial.
The "Last" values are -3 and +1. We multiply these and get -3, which is the last value of the polynomial.
You have to play around with different factors to get this to work.
Once you have the factors, set them = to 0 and solve.
2007-02-03 05:38:38
·
answer #5
·
answered by tma 6
·
0⤊
0⤋
Use
D= (B^2) - 4AC
Here B= -2, A= 8 and C= -3
D= 4- (4(8)(-3))= 100
x= (-B + (D)^ 1/2)/2A
and x= (-B- (D)^1/2)/2A
so x=3/4 and x= -1/2
2007-02-03 05:16:13
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
as it is a quadratic eqn, so ut will have 2 answers let: A and B. now yer eqn. is in the form ax^2 +bx+c right.[here a=8,b=(-2) and c=(-3)]. got it? good!
then put the formula [b+/- (b^2 -4ac)]/2a ok.[+/- means put + to get A and - to get B or vice versa.] A & B are the roots or answers . pls tremember it. dnt lose marks buddy exams r close. do well man!!
2007-02-03 05:25:23
·
answer #7
·
answered by Rishi k 2
·
0⤊
1⤋
x="(-B+or-squrt(B^2-(4*A*C)))/(2A)
X=--2+ root of (4- (-3*4*8))/2*8
=2+10/16=0.75
or=2-10/16=-0.5
answer is .75 and .5
or u can do it like that
8x^2-2x-3=(6x-3)(4/3x-1)=0
2007-02-03 05:29:02
·
answer #8
·
answered by kater al nada 2
·
0⤊
1⤋